2012
DOI: 10.1186/1756-3305-5-125
|View full text |Cite
|
Sign up to set email alerts
|

CO2 flagging - an improved method for the collection of questing ticks

Abstract: BackgroundMost epidemiological studies on tick-borne pathogens involve collection of ticks from the environment. An efficient collection method is essential for large sample pools. Our main aim was to evaluate the efficacy of a new method, where traditional flagging was enhanced by the use of CO2 dispersed into the white flannel. The CO2 was spread through a rubber hose network inserted into the flag blanket. The research was conducted in spring, in March-April 2011 in two locations from Cluj County, Romania.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…In Experiment 1, I. ricinus nymphs were found to respond to elevated CO 2 concentrations in the surrounding air. This is in line with the results of Gherman et al (), who showed that adding CO 2 to a blanket to a concentration of 0.08% increased capture efficiency of I. ricinus , and Gray (), who showed that a trap baited with CO 2 caught I. ricinus larvae, nymphs and adults. Increased capture efficiency of I. ricinus is not necessarily the result of the attraction of ticks to the trap, but may also reflect increased activity of ticks induced by the CO 2 .…”
supporting
confidence: 90%
“…In Experiment 1, I. ricinus nymphs were found to respond to elevated CO 2 concentrations in the surrounding air. This is in line with the results of Gherman et al (), who showed that adding CO 2 to a blanket to a concentration of 0.08% increased capture efficiency of I. ricinus , and Gray (), who showed that a trap baited with CO 2 caught I. ricinus larvae, nymphs and adults. Increased capture efficiency of I. ricinus is not necessarily the result of the attraction of ticks to the trap, but may also reflect increased activity of ticks induced by the CO 2 .…”
supporting
confidence: 90%
“…Given that studies conducted in other states have demonstrated the presence of the POWV in the immature (nymph) stage of I. scapularis ticks (Anderson & Armstrong, ; Dupois et al., ; Mueller, ), the possibility that the sampling approach of our study may have resulted in an underestimation of the POWV/DTV tick infection rate should be considered. Future research should attempt to recover both adult and nymph I. scapularis ticks by methods such as seasonally appropriate tick drag sampling (Daniels, Falco, & Fish, ; Gherman et al., ; Ginsberg & Ewing, ; Schulze, Jordan, & Hung, ). Although infected ticks can be found all year‐round, tick recovery should also be considered when tick activity is greatest, March to mid‐May and from mid‐August to November (Brei et al., ; Gatewood et al., ; Ogden et al., ; Stafford, Cartter, Magnarelli, Ertel, & Mshar, ).…”
Section: Discussionmentioning
confidence: 99%
“…Sensilla cell responses to carbon dioxide have been recorded in A. americanum , A. maculatum , D. variabilis [110], and A. variegatum ticks [39]. Lab and field bioassays have also demonstrated the attractive quality of carbon dioxide to A. americanum [36], A. hebraeum [111], A. triguttatum [112], A. variegatum [109], D. andersoni [113], D. variabilis [36], I. dammini [113], I. ricinus [114], I. scapularis [115], R. microplus [28], and R. sanguineus [116]. Attractive behavioral responses to acetone and ammonia dissolved in water have been recorded for A. americanum [36] and to acetone alone in A. hebraeum [109].…”
Section: Chemistry Of Host Kairomonesmentioning
confidence: 99%